Topics on Applied Econometrics - Tarun Dass (Planning Commission, Government of India)
The most common measure of aggregate economic activity is the Cross National Product (GNP). There are two approaches to measure GNP. Under value added approach, GNP equals sum total of all value added for all products. Net value added (NVA) is the difference between total sales and total purchases (i.e. intermediate products) of a firm.
Planning Commission, Government of India
Keywords: Transport Modelling Demand Analysis Size Distribution on Income, Wealth and Consumption Measurement of Poverty and Inequality National Income and Growth Production, Cost and Supply Functions Supply and Demand for Money, Exports and Imports